At mageskifte det timelige med det åndelige - Ingesman, Per (Religionsvidenskabeligt Tidsskrift, 1996)
"To exchange the Temporal with the Spiritual: Religious Gift-Giving in the Western European Middle Ages" - The main part of the article concentrates on a chantry founded in 1512 by Danish Archbishop Birger Gunnersen of Lund. The chantry was, by all standards, a magnificent enterprise: by the number of tenant farmsteads - about 90 - being given to the foundation; by the number of horae, masses, vigils, and anniversaries that were to be sung and read in the chantry; and, finally, by the number of individuals - more than a hundred mentioned by name - for whose souls prayers were to be said during the masses. It is shown that the chantry has the sarcophagus of the archbishop as its centre, åhysically as well as liturgically. The chantry represents, therefore, the same "cult of remembrabce" that Samuel K. Cohn has found in Italian renaissance cities after The Black Death. The foundation document, called "Sanctuarium Birgerrianum", is analyzed in order to uncover the religious ideas behind the foundation. Here it is concluded that although the archbishop was able to set up a highly sophisticated litugical programme, his personal religion was what Eamon Duffy calls "traditional religion". It has a do ut des thinking as its central idea, and so this case study shows the relevance of using Marcel Mauss' theory of gift-giving in a Danish context.